Innovations in sustainable energy and technology proceedings of ISET 2020 - Muthukumar, P.; Sarkar, Dilip Kumar; De, Debasis; De, Chanchal Kumar (Singapore Springer, 2021)
This book presents best selected research papers presented at Innovation in Sustainable Energy and Technology India (ISET 2020), organized by Energy Institute Bangalore (A unit of RGIPT, an Institute of National Importance), India, during 3–4 December 2020. The book covers various topics of sustainable energy and technologies which includes renewable energy (solar photovoltaic, solar thermal and CSP, biomass, wind energy, micro hydro power, hydrogen energy, geothermal energy, energy materials, energy storage, hybrid energy), smart energy systems (electrical vehicle, cybersecurity, charging infrastructures, IOT & AI, waste management, PHEV (CNG/EV) and mobility (smart grids, IOT & AI, energy-efficient buildings, mart agriculture).
Chapter 1. WattCastLSTM – Power Demand Forecasting using Long Short Term Memory Neural Network -- Chapter 2 -- Thermodynamic Analysis of Solar Photovoltaic/Thermal System (PVT) for Air-Conditioning Applications -- Chapter 3. PbS Nanoparticle Sensitized Fe-Doped Mesoporous TiO2 Photoanodes for Photoelectrochemical Water Splitting -- Chapter 4. In situ Nickel (Ni) doped Co3O4 nanostructure: an efficient electrocatalyst for hydrogen evolution -- Chapter 5. Aerodynamic Performance Enhancement and Optimization of a H-rotor Vertical Axis Wind Turbine -- Chapter 6. CFD Analysis of a Straight Bladed Darrieus Vertical Axis Wind Turbine Using NACA 0021 Aerofoil -- Chapter 7. Fabrication of Dye Sensitized Solar Cell Based on Natural Dye Sensitizer and ZnO Nanoflowers Photoanode -- Chapter 8. Effect of Longitudinal Fin Configuration on the Charging and Discharging Characteristics of a Horizontal Cylindrical Latent Heat Storage System -- Chapter 9. Fabrication of Catalytic Sheet Filter of V2O5-WO3/TiO2 supported-SiC for Selective Catalytic Reduction of NOx emission from Combustion Engine -- Chapter 10. CEPSO based Load Frequency Control of Isolated Power System with Security Constraints.
Electronic reproduction
Keywords: Clean energy -- Congresses; Renewable energy sources -- Congresses; Electronic books